An analysis of the intellectual freedom content of the Philippine Radical Papers Collection at the University of the Philippines Diliman Main Library - Calaycay, Angelica C.; Tarlit, Rodolfo Y. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2006)
The Philippine Radical Papers Collection at the University of the Philippines Diliman Main Library is primarily a collection of alternative materials from various individuals and organizations, mainly to express their criticisms against the government especially during the period of martial law. Organizing the collection and making it accessible is a significant contribution to our society, for first-hand references on martial law and the people and organizations who struggled for the restoration of democracy in the country can be accessed here.
This study sought to describe and analyze the intellectual freedom content of the collection, in relation to other factors such as the creator(s) of the records, the data when it was created or published, and the form of the document. Symbols of intellectual freedom namely freedom of the press, freedom of speech, academic freedom, freedom of thought, freedom to read and the translation of these symbols in Filipino were noted from the records. These symbols were categorized according to the provision of the Library Bill of Rights, created by the American Library Association.
This study found that the materials in the collection are mostly favorable to intellectual freedom, and that the most prominent symbols are freedom of speech, freedom of the press and academic freedom. The relevant records in the collection mostly came from political organizations, and mostly created during the decade of 1970-1979. Intellectual freedom is a necessity in the creation, access, and dissemination of thought, to which the library plays an important role. Intellectual freedom also empowers libraries in their role in providing service, education and mediation among the information needs of its patrons by facilitating for the effective circulation of ideas. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Main Library (Diliman).; Radicalism -- Philippines; Intellectual Freedom -- Philippines